Pengaruh Jarak Tanam Dan Dosis Pupuk Nitrogen Terhadap Pertumbuhan Bud Chip Tebu (Saccharum Officinarum L.) - Arif Al Qudry; irsal irsal; Revandy IM Damanik (Jurnal Agroekoteknologi, 2016)
The research was conducted at experimental field of Tanjung Jati estate Binjai PTPN II (± 50 m asl) in August 2014 - January 2015 using a randomized block design with two factors, the first factor was plant spacing (33 cm, 40 cm, 47 cm) with center to center distance (CCD) was 135 cm and the second factor was dose of nitrogen fertilizer (45, 90, 135, 180 kg N / ha). The observation variables measured were plant height, stem diameter, number of leave, number of tilles, number of segment, leaf area, shoot dry weight, root dry weight.The results showed that the treatment plant spacing gave significant effec to  stem diameter, the number of tiller, number of segments, and leaf area. the treatment of dose of nitrogen fertilizer gave significant effect to the stem diameter, number of tiller and leaf area. Interaction treatment only significantly effected for steam diameter 1  MAP and the number of section 5 MAP. The research shows that the best plant spacing was 47 cm x 135 cm and dose of nitrogen fertilizer was 90 kgN/ha increase growth bud chip sugarcane.